Educator Character Construction in the Context of the Merdeka Curriculum: A Study of the Thought of K.H. Hasyim Asy'ari and Parker J. Palmer - Tasurun Amma; Ahmad Zainuri; Fitri Oviyanti (Universitas Muhammadiyah Malang, 2024)
This study aims to analyze the concept of educator character according to K.H. Hasyim Asy'ari and Parker J. Palmer and its relevance in the Merdeka Curriculum in Indonesia, including several aspects, namely the character of educators from the perspectives of K.H. Hasyim Asy'ari and Parker J. Palmer, this study examines the comparison and integration of the ideas of two prominent figures and explores their relevance within the framework of the Merdeka Curriculum. The research employs a qualitative methodology, utilizing a literature review approach, with data sourced from the writings of these figures alongside additional supporting references. The data collected were analyzed through content analysis, comparative analysis, and thematic analysis to draw conclusions regarding the educator characteristics proposed by K.H. Hasyim Asy'ari and Parker J. Palmer, as well as their relevance to the Merdeka Curriculum. The findings revealed that the perspectives of K.H. Hasyim Asy'ari and Parker J. Palmer on educator character present distinct yet mutually complementary approaches to education. The concept of Mu'allim al-Fadhil from K.H. Hasyim Asy'ari emphasizes moral integrity, spiritual leadership, and Islamic values such as compassion, manners, and social responsibility. Meanwhile, Parker J. Palmer emphasizes authenticity, meaningful relationships, and emotional and spiritual intelligence in the concept of The Authentic and Relational Educator (ARE). Both approaches are relevant to the Merdeka Curriculum, which focuses on holistic learning, character development, and value-based personal facilitation to create a competent and virtuous generation.